2016
DOI: 10.1177/1525822x16663162
|View full text |Cite
|
Sign up to set email alerts
|

The Interviewer in the Respondent’s Shoes: What Can We Learn from the Way Interviewers Answer Survey Questions?

Abstract: Previous research shows that interviewers to some extent fail to expend the effort that is needed to collect high-quality survey data. We extend the idea of interviewer satisficing to a related task, in which the interviewers themselves answer survey questions. We hypothesize that interviewers who self-administer the questionnaire in a careless manner, also will not apply themselves fully to the task of administering survey interviews. Based on interviewer and respondent data from the sixth round of the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Poorly motivated interviewers may broadcast their low levels of motivation to respondents, who will consequently perceive the interview as less pleasant. Research has shown that interviewees' and interviewers' response behavior are related (Pickery and Loosveldt 2001; Wuyts and Loosveldt 2017): Item nonresponse is higher if interviews are administered by interviewers who themselves did not answer this item in a related survey, and interview speed is higher if interviewers themselves were faster at completing the survey. This may be because interviewers who are not interested in the study may want to finish their task faster or presume that the respondent is also not interested and try to conduct the interview as quickly as possible.…”
Section: Background and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Poorly motivated interviewers may broadcast their low levels of motivation to respondents, who will consequently perceive the interview as less pleasant. Research has shown that interviewees' and interviewers' response behavior are related (Pickery and Loosveldt 2001; Wuyts and Loosveldt 2017): Item nonresponse is higher if interviews are administered by interviewers who themselves did not answer this item in a related survey, and interview speed is higher if interviewers themselves were faster at completing the survey. This may be because interviewers who are not interested in the study may want to finish their task faster or presume that the respondent is also not interested and try to conduct the interview as quickly as possible.…”
Section: Background and Literaturementioning
confidence: 99%
“…Interviewer effects of similar size have been reported for other survey outcomes as well, e.g., social network modules (Josten and Trappmann 2016; van Tilburg 1998) and interview speed (Loosveldt and Beullens 2013; Wuyts and Loosveldt 2017).…”
mentioning
confidence: 99%